2011
DOI: 10.1152/ajplung.00342.2010
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and heterogeneity of the pulmonary endothelial glycocalyx measured by atomic force microscopy

Abstract: O'Callaghan R, Job KM, Dull RO, Hlady V. Stiffness and heterogeneity of the pulmonary endothelial glycocalyx measured by atomic force microscopy. Am J Physiol Lung Cell Mol Physiol 301: L353-L360, 2011. First published June 24, 2011 doi:10.1152/ajplung.00342.2010.-The mechanical properties of endothelial glycocalyx were studied using atomic force microscopy with a silica bead (diameter ϳ18 m) serving as an indenter. Even at indentations of several hundred nanometers, the bead exerted very low compressive pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 37 publications
(56 reference statements)
4
53
0
Order By: Relevance
“…Based on studies from vascular beds of systemic vessels, the glycocalyx has been shown to act as a sieve allowing transendothelial transport of low-molecularweight solutes, inhibiting red blood cell and neutrophil adhesion and extravasation, and as a mechanotransducer (67,113). However, characterization of the glycocalyx in the pulmonary microcirculation remained controversial as most of the studies relied on using enzymatic degradation of glycocalyx constituents (24, 31, 35, 37, 45,71,102,130). Recently, Schmidt and coworkers (125) used a model of intravital microscopy in the intact, ventilated mouse (136) to demonstrate that the pulmonary endothelial glycocalyx is ϳ1.7 m thick, i.e., around two to three times the value of the glycocalyx in the systemic circulation.…”
Section: Glycocalyxmentioning
confidence: 99%
“…Based on studies from vascular beds of systemic vessels, the glycocalyx has been shown to act as a sieve allowing transendothelial transport of low-molecularweight solutes, inhibiting red blood cell and neutrophil adhesion and extravasation, and as a mechanotransducer (67,113). However, characterization of the glycocalyx in the pulmonary microcirculation remained controversial as most of the studies relied on using enzymatic degradation of glycocalyx constituents (24, 31, 35, 37, 45,71,102,130). Recently, Schmidt and coworkers (125) used a model of intravital microscopy in the intact, ventilated mouse (136) to demonstrate that the pulmonary endothelial glycocalyx is ϳ1.7 m thick, i.e., around two to three times the value of the glycocalyx in the systemic circulation.…”
Section: Glycocalyxmentioning
confidence: 99%
“…40 Moreover, it has been demonstrated that it is possible to detect length and grafting density of the brush layer on living cells, 65,66 or even to distinguish between cancerous and healthy cells' brushes, 67 thanks to the sensitivity of micrometric spherical probes provided by their wider surface area.…”
Section: Colloidal Spherical Probesmentioning
confidence: 99%
“…Here, the role of the ECM per se is not well understood. However, in addition to well-known endothelial barrier signaling pathways, there is recent evidence that the glycocalyx plays a role in barrier functions that may be modulated by mechanical forces (43,87,115,136).…”
Section: Materials Matrix and Mechanobiologymentioning
confidence: 99%